Incidência da dengue em menores de quinze anos de idade no período de 2003 a 2013 no Estado do Tocantins - Ribeiro, Mirelly da Silva (2015)
Dengue is an acute febrile disease caused by an arbovirus that belongs to the family Flaviridae and transmitted by the bite of the mosquito Aedes aegypti. It is a descriptive epidemiological study, restrospectivo, ecological with the use of secondary data on the incidence of dengue in children under 15 years from 2003 to 2013, in order to describe its epidemiological characteristics, developed in the three largest urban centers State of Tocantins. The present study identified 8,211 cases in children under fifteen years. The classic form occurred in 99.2%, and 0.8% have progressed to severe dengue, and for both clinical forms most occurred in urban areas (98.4% and 100.0%). Classical Dengue (p = 0.3814), and severe (p = 0.3211), occurred in both men and women equally. Both forms of the disease is more prevalent in mulatto (63.8% and 68.3%) (p = 0.0001). The most affected age group was 10-14 (46.3%) for the classical form (p = 0.0001) and 5-9 years (50.7%) to severe form of dengue (p = 0, 0001). The dengue incidence rate in children under 15 years remained at endemic levels, but growing and there is a positive and statistically significant correlation (r = 0.8; p = 0.002) between the year and the incidence of cases. We conclude that in the three largest urban centers in the State of Tocantins Dengue in children under 15 years is endemic urbanbased, incident in brown individuals, with equal incidence in both sexes. Being the age group most affected those aged 10-14 years to classic dengue and 5 - 9 years for severe dengue. The present study observed that in Tocantins state is increasing the incidence rate in children under 15 years.